Advances in Stored Product Protection. Proceedings of the 8th International Working Conference on Stored Product Protection, Yo 2003
DOI: 10.1079/9780851996912.0410
|View full text |Cite
|
Sign up to set email alerts
|

Impact of IPM practices on insect populations in retail pet stores.

Abstract: Stored-product insect infestations in retail pet stores cost pet food manufacturers millions of dollars annually, but there are no studies documenting the effectiveness of pest management practices in pet stores. Our study was designed to determine species associated with eight pet stores in Kansas, USA, and to evaluate the impact of chemical and non-chemical intervention on insect populations. Food and pheromone-baited traps were used to estimate numbers of stored-product beetles and the Indian meal moth, Plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Data shown here strongly suggest that level of sanitation before insecticide application was more important than use of a particular insecticide. Excellent sanitation also forces insects to move around ( Roesli et al 2003 ; Toews et al 2005a ) and could thereby increase the potential for insecticide contact. Campbell and Hagstrum ( 2002 ) found that T. castaneum spend much more time in food patches than outside food patches.…”
Section: Discussionmentioning
confidence: 99%
“…Data shown here strongly suggest that level of sanitation before insecticide application was more important than use of a particular insecticide. Excellent sanitation also forces insects to move around ( Roesli et al 2003 ; Toews et al 2005a ) and could thereby increase the potential for insecticide contact. Campbell and Hagstrum ( 2002 ) found that T. castaneum spend much more time in food patches than outside food patches.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that insect captures will be greater under refugia, in corners, along walls and near food sources (Arbogast et al, 2002;Campbell & Hagstrum, 2002;Toews et al, 2005a). In the absence of contact pesticide usage, good sanitation in the warehouse or retail environment increases the number of insects captured in traps (Roesli et al, 2003a;Toews et al, 2005a). These data show that pesticide usage is another factor that must be considered when evaluating population indices based on pheromone trapping captures.…”
Section: Discussionmentioning
confidence: 95%
“…For example, excellent mortality to T. castaneum as a result of cyfluthrin exposure on steel, concrete and painted surfaces has been thoroughly documented under laboratory conditions (Arthur, 1994a(Arthur, ,b, 1998(Arthur, , 1999a(Arthur, ,b, 2000. Previous studies have attributed population suppression in grain processing and retail establishments to cyfluthrin use (Roesli et al, 2003a;Toews et al, 2006a). Barrier treatments, consisting of a narrow band of cyfluthrin around a protected area, have been previously used to suppress trap captures of structure-infesting ants such as Iridomyrmex humilis (Mayr) (Hymenoptera: Formicidae) (Rust et al, 1996;Scharf et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cleaning procedures followed by the mill sanitarians may inßuence insect movement through increased searching for food patches, which potentially increases their chances of contacting the applied aerosols (Roesli et al 2003). However, milling facilities have considerable structural complexity because of different types of processing equipment and are continuously generating spillage and food residues.…”
Section: Discussionmentioning
confidence: 99%